Measurement Model of Brand Loyalty for Palm Cooking Oil Market in Malaysia - Shaban, Omar Kassim A.; Liu, Yao; Mohd Ridzuan, Darun (2017)
This study examines how Prahalad’s market framework influenced brand loyalty in the base of the Palm Cooking Oil market in Malaysia. Although there is a positive correlation between brand awareness and brand loyalty, no studies have quantitatively examined all of Prahalad’s 4As as a set of independent variables influencing the dependent variable brand loyalty. The previous studies did not address a statistically significant standardized parameters estimate existing between awareness and brand loyalty. This Rstudy addresses this gap in the research literature through its investigation of the simultaneous impact of Prahalad’s 4As on brand loyalty of Palm Cooking Oil in Malaysia. The study validated earlier studies, finding a statistically significant standardized parameters estimate existing between awareness and brand loyalty. These findings directly support Prahalad’s initial 4As framework as it relates to awareness and affordability.